Drive and Instinct—How They Produce Relatedness and Addiction - Ringwood, Thomas; Cox, Lindsay; Felldin, Breanna; Kirsch, Michael; Johnson, Brian (Frontiers in Psychology, 2021)
Addictive drugs are responsible for mass killing. Neither persons with addiction nor the general populace seem conscious of the malevolence of governments and drug dealers working together. How could this be? What is the place of psychoanalysis in thinking about deaths from addiction and in responding to patients with addiction? To answer these questions we revise concepts of SEEKING, drive, instinct, pleasure and unpleasure as separable. We review the neurobiological mechanism of cathexis. We discuss how addictive drugs take over the will by changing the SEEKING system. We review how opioid tone in the central nervous system regulates human relationships and how this endogenous hormonal system is modified by external opioid administration. We differentiate the pleasure of relatedness from the unpleasure of urgent need including the urgent need for drugs. We show how addictive drug induced changes in the SEEKING system diminish dopaminergic tone, reducing motivation to engage in pursuit of food, water, sex, sleep and relationships in favor of addictive drugs. With this neuropsychoanalytic understanding of how drugs work we become more confidently conscious of our ability to respond individually and socially.